Implementasi Metode Backpropagation untuk Mengenali Teks pada Natural Scene Image - Imam Ghozali; Tibyani Tibyani; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Text in images contain useful information. Text detection in Natural Scene Image (NSI) becomes an important part of research on text information extraction (TIE). For getting information on the NSI there are various challenges, such as determining the text region in a complex background to recognize various kinds of text that has a variety of shapes, sizes, colors and others. The results of TIE can be implemented in many ways, one of them system can to help blind people to recognize product label or recognize text is around them. To recognize text on the NSI is a composite of two research topics, the first topic is determination of the text region or text detection and second topic is recognizing character of text or character recognition. In this research will focus on recognizing character using backpropagation method. Results of tests is 44.00%, this is influenced by the features extracted from the results of image binerization, many image data has a noise.